Willingness to Pay for Halal-Certified Livestock Products in South Kalimantan: An Extended Theory of Planned Behavior Approach - H. Apedro; M. Riyadhi; M. Y. Syihabuddin; A. S. Imanullah; N. Mufidah; M. Archadiya; M. Yuniar (Faculty of Animal Science, IPB University, 2026)
Halal certification has become a key signal of religious compliance and quality assurance in Muslim-majority food markets, yet consumers’ willingness to pay (WTP) a price premium for certified livestock products remains unevenly understood at the local level. This study examined WTP for halal‐certified meat, poultry, eggs, and milk in South Kalimantan, Indonesia, using an extended Theory of Planned Behavior (TPB) that incorporated religious commitment as an additional driver and moderator. Primary cross-sectional data were collected via an online questionnaire from 300 Muslim consumers, screened for recent purchases of livestock products, and were analyzed using partial least squares structural equation modelling. The model connected attitude, subjective norms, perceived behavioral control, and religious commitment with WTP, and examined whether religious commitment enhanced the influence of social pressure and perceived control on WTP. The results showed that attitude was the most robust predictor of willingness to pay, followed by perceived behavioral control and subjective norms, while religious commitment exerted a smaller but significant direct effect on WTP. Religious commitment enhanced the positive relationships between subjective norms and WTP as well as between perceived behavioral control and WTP. These findings indicated that the acceptance of prices for halal-certified livestock products was influenced by positive assessments, perceived purchase convenience, and the extent of consumers' religious commitment. The study concluded that policies and marketing methods that increased the visibility, credibility, and alignment of certification with customers' religious beliefs could elevate WTP for halal-certified livestock products.